Re-conceptualize CSR in the context of an African emerging country. The case of circular economy in Cameroon - (:unkn) unknown (My University, 2017)
Developing countries have to deal with increasing environmental issues which are related to their lightning urbanization, so they need to figure out how they can combine economic development and protection of the environment. In order to deal with such a challenge, socioeconomic actors develop innovative approaches of CSR that cannot be conceptualized with current theoretical models which mainly come from works related to northern countries. Thanks to a field research carried out on circular economy in Cameroon and a qualitative analysis, we propose an original theoretical model, more relevant for conceptualizing CSR in the context of an African emerging country
Keywords: African Research